The role of the nurses in the special care nursery: their own descriptions - Fenwick, Jennifer; Barclay, Lesley; Schmied, V. (Elsevier Ltd, 2003)
This paper presents new findings resulting from a thematic analysis of interview data collected from Australian nurses working in the Special Care Nursery (SCN). This work was part of a programme of research, which has investigated theimpact of neonatal nursery care on parent's disrupted transition to parenthood. The particular focus of this group ofstudies was women's experiences of mothering in the SCN. The findings suggest that the ideology of the infant as anindividual and independent from the mother and family needs continued critique.